200-grade sludge fly ash ceramsite composition based on solid waste and manufacturing method thereof
By utilizing shale, sludge, and fly ash to manufacture 200-grade sludge-fly ash ceramsite, the problems of land and energy waste and waste residue restrictions associated with traditional building materials have been solved, achieving efficient utilization of solid waste resources and preparation of green building materials.
Patent Information
- Application Number
- CN202511045123.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-10-31
AI Technical Summary
Existing building materials use a large amount of clay and energy in their manufacturing process, resulting in waste of land resources and environmental pollution. At the same time, the amount of waste residue added in traditional ceramsite production affects the quality of building materials and limits their application.
Using shale, sludge, and fly ash as the main raw materials, 200-grade sludge and fly ash ceramsite is manufactured through processes such as vertical mill grinding, stirring, and rotary kiln sintering. Biomass gas is used as a heat source to form high-temperature sintering and cooling screening, thus producing ceramsite with excellent performance.
It achieves efficient utilization of solid waste resources, reduces costs, reduces dependence on land, and produces building materials with low thermal conductivity, earthquake resistance, sound insulation, and environmental protection, meeting the requirements of green building.
Smart Images

Figure CN120864865A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of comprehensive utilization of solid waste resources, specifically relating to a 200-grade sludge fly ash ceramsite composition based on solid waste and its manufacturing method. Background Technology
[0002] In recent years, the construction of "zero-waste cities," which integrates urban development and solid waste management, has vigorously promoted waste reduction, resource recovery, and harmless disposal, leveraging the synergistic effects of pollution reduction and carbon reduction. It aims to achieve carbon peaking and carbon neutrality by coordinating urban development and solid waste management. Meanwhile, traditional building construction primarily uses red bricks made from a mixture of shale, clay, or mortar, which wastes significant amounts of land and energy. Although lightweight wall blocks have been developed, they suffer from high investment costs, complex processes, and stringent technical requirements. Expanded clay aggregate (ECA) is one of the fastest-growing new building materials in recent years. With its low thermal conductivity, excellent thermal insulation performance, good sound absorption and insulation performance, high temperature resistance, aging resistance, acid and alkali resistance, environmental protection and energy saving, earthquake resistance, good durability, as well as a series of advantages such as high activity, multiple micropores, large specific surface area and strong adsorption capacity, it is widely used in the construction field. However, traditional ceramsite requires a large amount of clay in the manufacturing process, which is somewhat harmful to the environment and consumes the land resources on which people depend for survival. Existing technologies use shale alone to make ceramsite products, or add industrial waste as an additive. However, the amount of waste added directly affects the quality of building materials, which leads to strict restrictions on the production and application of this type of building material. Summary of the Invention
[0003] To address the aforementioned problems in the existing technology, the present invention aims to provide a 200-grade sludge fly ash ceramsite composition based on solid waste and its manufacturing method. This method utilizes solid waste to manufacture 200-grade sludge fly ash ceramsite, making full use of solid waste resources, and features a simple process and low cost.
[0004] The technical solution adopted in this invention is as follows: First technical solution: Provides a 200-grade sludge fly ash ceramsite composition based on solid waste, comprising the following components: shale, sludge and fly ash; The allocation of each group according to weight percentage is as follows: Shale 38%–50%; 30%–40% sludge; fly ash 20%–25%; The shale mentioned therein is a muddy shale composed of main components and auxiliary components, and the muddy shale contains more than 40% clay mineral components by total weight; The main components are red shale, black shale, and green shale, and the auxiliary components are kaolin and bentonite.
[0005] Furthermore, the shale comprises the following components by weight percentage: 50% ~ 60% Si02, 17% ~ 23% A1203, 5% ~ 8% Fe203, 1% ~ 3% MgO, 5% ~ 10% CaO and 1% ~ 3% (Na2CHK2O).
[0006] Furthermore, the shale comprises the following components by weight percentage: 58%Si02, 21%A1203, 6.8%Fe203, 2.4%MgO, 9%CaO, 1.5%Na20 and 1.3%K20.
[0007] The second technical solution provides a method for preparing a 200-grade sludge fly ash ceramsite composition based on solid waste, used to manufacture the 200-grade sludge fly ash ceramsite composition based on solid waste in the first technical solution above, comprising the following steps: S1, Material preparation, collecting and selecting fine sludge, shale, sludge and fly ash raw materials; S2 uses a vertical mill to grind shale, sludge and fly ash raw materials respectively; S3, the ground raw materials are screened to obtain shale, sludge and fly ash materials with a mesh size of less than 150; S4, according to the proportion of the 200-grade sludge fly ash ceramsite composition based on solid waste in the first technical solution, weigh the shale, sludge and fly ash materials respectively, and transport them to the mixer for thorough mixing to obtain mixed raw materials, which are then transferred to S5 or S6; S5, transport the mixed raw materials to the storage tank for storage and later use; S6 conveys the mixed raw materials to the three-stage drive variable diameter rotary kiln; S7. After drying, the mixed raw materials are preheated through the preheating heat plate. The temperature of the preheating heat plate is gradually increased from 120℃ to 270℃, and the preheating time is 40 to 45 minutes. S8, transfer to the firing zone, sinter at a temperature of 1120-1170℃ for 7-12 minutes, and obtain sludge fly ash ceramsite by sintering. S9, the sludge fly ash ceramsite is fed into the cooler, and the cooling time can be 25 to 30 minutes, until the temperature of the sludge fly ash ceramsite drops below 100°C; S10, screen out ceramsite sand with a particle size of 0mm < ≤ 5mm, ceramsite with a particle size of 5mm < ≤ 25mm, and ceramsite blocks with a particle size of 25mm < ≤ 40mm; S11, Inspection: Ceramsite, ceramsite particles, and ceramsite blocks are stored separately. S12, ceramic sand is used as building insulation mortar; ceramic pellets and ceramic blocks are used as building materials or as adsorbent materials.
[0008] Furthermore, the three-stage transmission variable diameter rotary kiln is composed of three kilns of different diameters connected to each other. The three kilns of different diameters are: a drying kiln, a preheating kiln, and a sintering kiln.
[0009] Furthermore, the drying kiln of the three-stage transmission variable diameter rotary kiln has a diameter of 1.7 meters, the preheating kiln has a diameter of 2.1 meters, and the sintering kiln has a diameter of 2.5 meters.
[0010] Furthermore, the total length of the three-stage transmission variable diameter rotary kiln is 77 meters to 112 meters, of which the length of the drying kiln is 20 meters to 30 meters, the length of the preheating kiln is 20 meters to 30 meters, and the rest are sintering kilns.
[0011] Furthermore, the total length of the three-stage transmission variable diameter rotary kiln is 77 meters, of which the drying kiln has a straight length of 29 meters, the preheating kiln has a length of 27 meters, and the rest are sintering kilns.
[0012] Furthermore, the rotary kiln rotates at a speed of 1.5 rpm.
[0013] Finally, the rotary kiln uses biomass gas as the combustion source, which provides a heat source for the firing of sludge fly ash ceramsite after combustion. The biomass fuel gas is generated by a biomass briquette pellet gasifier.
[0014] The beneficial effects of this invention are as follows: a 200-grade sludge fly ash ceramsite composition based on solid waste and its manufacturing method, comprising, by weight percentage, 38%–43% shale, 30%–40% sludge, and 20%–25% fly ash; wherein the shale is a muddy shale mainly composed of red shale, black shale, and green shale, with kaolinite and bentonite as auxiliary components, containing a total weight of clay minerals greater than 40%; the manufacture of 200-grade sludge fly ash ceramsite using solid waste makes full use of solid waste resources, and the process is simple and cost-effective. Attached Figure Description
[0015] Figure 1 This is a flowchart illustrating the method for preparing a 200-grade sludge fly ash ceramsite composition based on solid waste, according to Embodiment 1 of the present invention. Detailed Implementation
[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0017] To address the problems existing in the prior art and to meet the current national strategic goals of achieving "zero-waste cities" and rural revitalization, this invention provides a composition for converting solid waste into 200-grade sludge fly ash ceramsite, which can be used in green building, green planting, and green aquaculture materials, as well as a method for manufacturing 200-grade sludge fly ash ceramsite. Specifically, it provides a 200-grade sludge fly ash ceramsite composition based on solid waste and its manufacturing method. The first technical solution first conceives of a 200-grade sludge fly ash ceramsite composition based on solid waste, whose main components include shale, sludge, and fly ash. By utilizing solid waste to manufacture 200-grade sludge fly ash ceramsite, it fully utilizes solid waste resources, responds to the strategic goals of "zero-waste cities" and rural revitalization, leverages the synergistic effect of pollution reduction and carbon reduction, coordinates urban development and solid waste management, and strives to promote carbon peaking and carbon neutrality.
[0018] The allocation of each group according to weight percentage is as follows: Shale 38%–50%; 30%–40% sludge; fly ash 20%–25%; The shale used is muddy shale composed of main and auxiliary components, and the muddy shale contains more than 40% clay minerals by weight. The main components of shale are red shale, black shale, and green shale, while the auxiliary components are kaolin and bentonite.
[0019] The present invention uses solid wastes such as fly ash, sludge, red mud, fly ash, construction waste, sulfonated mud, titanium gypsum, phosphogypsum, molybdenum tailings, gold tailings, and coal gangue as raw materials. It utilizes the mineral components silicon, iron, aluminum, magnesium, sodium, potassium, calcium, and carbon contained in these solid wastes as the main components of ceramsite. The mineral components that make up the ceramsite are mainly oxide components.
[0020] The oxide components that make up ceramsite can be formulated using the following proportions: The composition consists of 50%–60% silicon oxide, 5%–8% iron oxide, 17%–23% aluminum oxide, 1%–3% magnesium oxide, 1%–3% sodium oxide, 1%–3% potassium oxide, 5%–10% calcium oxide, and 1%–3% carbon oxide, with building foundation soil, subway tunnel soil, shale, and kaolin as auxiliary materials. Solid wastes such as fly ash, sludge, red mud, construction waste, sulfonated mud, titanium gypsum, phosphogypsum, and molybdenum tailings are collected, crushed, aged, fermented, and screened. The mixture is then fed into a material mixing chamber, granulated, sintered in a rotary kiln, unloaded, cooled, screened, inspected, and stored to obtain Grade 200 sludge fly ash ceramsite.
[0021] Specifically, the shale in this invention, expressed as a chemical formula by weight percentage, mainly consists of the following components: 50% ~ 60% Si02, 17% ~ 23% A1203, 5% ~ 8% Fe203, 1% ~ 3% MgO, 5% ~ 10% CaO and 1% ~ 3% (Na2CHK2O).
[0022] For example, the specific parameters of shale during the implementation process can be composed of the following components by weight: 58%Si02, 21%A1203, 6.8%Fe203, 2.4%MgO, 9%CaO, 1.5%Na20 and 1.3%K20.
[0023] The second technical solution: A method for preparing a 200-grade sludge fly ash ceramsite composition based on solid waste is proposed, specifically used to manufacture the 200-grade sludge fly ash ceramsite composition based on solid waste in the first proposed technical solution. The proposed operation steps are as follows: The process involves collecting shale, sludge, and fly ash, drying and crushing them, screening the shale, sludge, and fly ash powders, mixing them in proportion, feeding them into a material storage tank, stirring and granulating them, sintering them in a rotary kiln, unloading them, cooling them, screening them, inspecting them, packaging them, and shipping them out of the factory.
[0024] In actual operation, follow these steps: The first step is to select sludge, fly ash, and shale raw materials. Specifically, prepare the materials first, and then collect and select fine sludge, shale, and fly ash raw materials from the prepared materials. Collect sludge and fly ash, and mine muddy shale containing more than 40% clay minerals, mainly red shale, black shale, and green shale, supplemented by kaolin and bentonite.
[0025] 1) Shale: Shale is composed of SiO2, Al2O3, Fe2O3, MgO, CaO, and Na2CHK2O. Their weight percentages are 50%–60% SiO2, 17%–23% Al2O3, 5%–8% Fe2O3, 1%–3% MgO, 5%–10% CaO, and 1%–3% (Na2CHK2O).
[0026] (ii) The composition of the sludge is as follows: 1. Clay content: The clay content in sludge is beneficial for its use as a building material. Generally, urban wastewater treatment plant sludge contains 20% to 30% inorganic matter, mainly oxides of silicon, iron, aluminum, and calcium, which are similar to the raw materials commonly used in many building materials. Even after incineration, these substances remain as incinerator ash. Therefore, the clay content in sludge can be used to manufacture building materials.
[0027] 2. Heavy Metals: The composition and properties of heavy metals in sludge vary greatly depending on the proportion of industrial wastewater and domestic sewage in different cities. After secondary treatment, more than 50% of the heavy metal ions in the wastewater are transferred to the sludge.
[0028] 3. Nutrients: Sludge contains rich nutrients, and its fertilizing effect is even better than that of farmyard manure such as cow dung.
[0029] ① Nitrogen salts: Nitrogen salts are essential nutrients for plant growth. Nitrogen in sludge exists in the form of organic and inorganic compounds, with organic nitrogen accounting for about 90%. However, organic nitrogen plays no role in plant growth and must be converted into nitrates before it can be utilized by microorganisms. Nitrogen is usually a limiting factor for the land application of sludge. Excessive use of nitrogen-containing sludge may lead to the transfer of unused nitrates to the surface or groundwater, thus having adverse effects on human health and the environment.
[0030] ② Phosphate: Every plant needs sufficient phosphorus for cell division and growth. Phosphorus exists in three forms: organic phosphorus, orthophosphate, and polyphosphate. The main form of phosphorus fertilizer uptake is phosphate released from the decomposition of organic matter, with orthophosphate, which can be absorbed by plants, being the dominant form.
[0031] ③ Potassium salts: Potassium is required for many functions of plants, including maintaining cell permeability, enhancing the plant's ability to resist damage, and assisting cells in transporting carbohydrates.
[0032] 4. Organic Matter: The organic matter in sludge is mainly composed of carbon (approximately 58% by mass, on a dry basis), with small amounts of hydrogen, oxygen, sulfur, and phosphorus. The main organic matter components are carbohydrates, proteins, and lipids. 5. Microorganisms: These can be categorized into bacteria, actinomycetes, viruses, parasites, protozoa, rotifers, and fungi. A significant portion of these microorganisms are pathogenic. Direct application of untreated sludge can transfer microorganisms and viruses to plants, surface water, and groundwater. Therefore, the removal of pathogenic microorganisms must be considered during sludge treatment.
[0033] III. Fly Ash: Fly ash from municipal solid waste incineration (hereinafter referred to as fly ash) is a secondary pollutant generated during the incineration process of municipal solid waste. Due to its content of heavy metals, dioxins, and other toxic and harmful pollutants, it is listed in the "National Hazardous Waste List (2021 Edition)," with the hazardous waste code "772-002-18." In the past, fly ash was mainly treated through solidification and landfill. However, landfilling not only occupies land but also poses a high risk of secondary pollution, making it an unsustainable treatment method. In recent years, during the promotion of "waste-free city" construction in my country, the treatment of fly ash has gradually shifted from landfill to resource utilization. The SiO2 and Al2O3 components contained in fly ash can serve as the skeleton material for ceramsite, thus providing a certain material basis for using fly ash to produce ceramsite. Furthermore, during high-temperature calcination, the heavy metals contained in fly ash can be fixed in the glass lattice of the calcined product, thereby ensuring that the content of leached heavy metals meets relevant requirements. Dioxins are completely decomposed at calcination temperatures above 1000℃, thus achieving the harmlessness and resource utilization of fly ash.
[0034] For example, shale containing the following components by weight percentage: 58% SiO2, 21% Al2O3, 6.8% Fe2O3, 2.4% MgO, 9% CaO, 1.5% Na2O and 1.3% K2O.
[0035] The sludge and fly ash used contain the following components in weight percentage: 48.9% SiO2, 16.0% Al2O3, 8.0% Fe2O3, 1.1% MgO, 4.1% CaO, and 1.9% (Na2O+K2O).
[0036] The second step involves pulverizing the powder using conventional coarse and fine powder pulverizers.
[0037] Vertical mills were used to grind and pulverize shale, sludge, and fly ash raw materials respectively.
[0038] The third step is to screen the ground raw materials to obtain shale, sludge and fly ash materials with a mesh size of less than 150. That is, shale and sludge fly ash smaller than 150 mesh are screened out from the crushed raw materials; raw materials with a diameter greater than 150 mesh are returned by conveyor belt for mixing and re-grinding. The fourth step involves weighing shale, sludge, and fly ash materials according to the proportion of the 200-grade sludge-fly ash ceramsite composition based on solid waste as planned in the first technical solution, and then conveying them to a mixer for thorough mixing. For example, the mixing ratio can be selected as follows: Shale:sludge:fly ash = 38%–50%:30%–40%:20%–25%; The mixture is thoroughly stirred in a mixer to obtain a mixed raw material, and then proceeded to step five or six.
[0039] The fifth step is to transport the mixed raw materials unloaded in the fourth step to the storage tank for storage when the sintering production line is not started or when the production line is in the process of firing in the furnace.
[0040] The sixth step is to transport the mixed raw materials unloaded in the fourth step to a three-stage transmission variable diameter rotary kiln before the production line is ready to start sintering, in order to preheat and refine the ceramsite. The three-stage transmission variable diameter rotary kiln is easier to operate and maintain, and the kiln temperature is more stable, thus ensuring stable product performance.
[0041] In a three-stage transmission rotary kiln with variable diameter, the order of the preheating chamber, sintering chamber, and drying kiln is usually: drying kiln → preheating kiln → sintering kiln. The material first enters the drying kiln, where it is dried using hot flue gas to remove moisture. Then it enters the preheating chamber, where the residual heat from the kiln tail flue gas is used to further heat the material, raising its temperature in preparation for subsequent calcination. Finally, it enters the sintering chamber (calcination zone), where the material undergoes physical and chemical changes at high temperatures to complete the sintering process.
[0042] A three-stage transmission rotary kiln with variable diameter can be constructed by connecting three kilns of different diameters; the three kilns of different diameters are: a drying kiln, a preheating kiln, and a sintering kiln.
[0043] Specifically, a three-stage drive variable-diameter rotary kiln can be selected with a total length of 77 meters to 112 meters. Within this kiln, the drying kiln has a diameter of 1.7 meters, the preheating kiln has a diameter of 2.1 meters, and the sintering kiln has a diameter of 2.5 meters. The total length of the three-stage drive variable-diameter rotary kiln is 77 meters to 112 meters, with the drying kiln having a length of 20 meters to 30 meters, the preheating kiln having a length of 20 meters to 30 meters, and the remainder being sintering kilns.
[0044] For example, a three-stage drive variable-diameter rotary kiln can be set to a total length of 77 meters, of which the drying kiln has a length of 29 meters, the preheating kiln has a length of 27 meters, and the rest is a sintering kiln. The three-stage drive variable-diameter rotary kiln can be set to a rotation speed of 1.5 rpm.
[0045] The three-stage transmission variable diameter rotary kiln uses biomass gas as the combustion source, and the combustion provides a heat source for the firing of sludge fly ash ceramsite. Biomass gas is generated by a biomass briquette pellet gasifier.
[0046] Step 7: After drying, preheat the mixed raw materials using a preheating heater. The temperature of the preheating heater is gradually increased from 120℃ to 270℃, and the preheating time is 40-45 minutes.
[0047] For example, it can be fed into the firing belt after preheating for 45 minutes.
[0048] Step 8: Transfer to the firing zone and sinter at a temperature of 1120-1170℃ for 7-12 minutes to obtain sludge fly ash ceramsite.
[0049] For example, it can be sintered at 1170℃ for 7 minutes.
[0050] The ninth step is to send the sludge fly ash ceramsite into a cooler, where the cooling time can be 25 to 30 minutes, until the temperature of the sludge fly ash ceramsite drops below 100°C.
[0051] Step 10: Screen again to remove ceramic sand with a particle size of 0mm < ≤ 5mm, ceramic pellets with a particle size of 5mm < ≤ 25mm, and ceramic blocks with a particle size of 25mm < ≤ 40mm.
[0052] The eleventh step is inspection; the clay sand, clay granules, and clay blocks are then stored in the warehouse separately.
[0053] In the twelfth step, among the finished products produced by the production line, ceramic sand is used as building insulation mortar; ceramic pellets and ceramic blocks are used as building materials or as absorbent materials.
[0054] The present invention relates to a method for preparing a Class 200 sludge fly ash ceramsite composition based on solid waste. The resulting Class 200 sludge fly ash ceramsite composition has the following advantages: 1) Using shale and sludge fly ash as raw materials to fire ceramsite not only saves the amount of clay used and conserves land, but also opens up a new way to utilize shale and sludge fly ash. 2) In the manufacturing method of sludge fly ash, there is no need to add industrial waste additives whose addition amount is strictly limited. Instead, solid wastes such as sludge fly ash are added. The addition amount is not strictly limited and will not affect the strength of the final building material. 3) Firing temperature (1120-1170°C): The surface of the fired ceramsite will form a glaze-like substance, which can make the ceramsite stronger.
[0055] The present invention will be described in detail below with reference to specific embodiments. Example 1
[0056] Clayey shale, primarily composed of red, black, and green shale, supplemented with kaolin and bentonite, was collected using conventional methods, along with sludge and fly ash. The shale was then ground using a conventional vertical mill for 3-5 minutes, followed by the following steps: (1) Screen out shale and sludge fly ash with a particle size of less than 150 mesh; (2) Take 45 parts of shale material, 30 parts of sludge and 25 parts of fly ash after screening in step (1) and mix them into a mixer to form a mixture; the mixing time is 3 to 7 minutes. (3) The mixture described in step (2) is fed from its mixer into a storage tank for preheating and firing. (4) The mixture discharged in step (3) is directly fed into the kiln head feeding port of the three-stage transmission variable diameter rotary kiln and rolled towards the kiln head for drying through the rotary kiln at different temperatures; its drying temperature is increased from the preheating temperature of 120°C to 270°C; then it enters the expansion zone sintering temperature (1120-1170°C) and is sintered to produce 200 grade sludge fly ash ceramsite. (5) The sludge fly ash ceramsite blocks sintered in step (4) are sent to a cooler for cooling. The cooling time is 25 to 30 minutes to reduce the temperature of the sludge fly ash ceramsite blocks to below 100°C. Then, they are screened by a screening machine for secondary classification. The sieved material with a particle size of 0 to 5 mm is ceramsite sand, which can be used as building insulation mortar. The material with a particle size of 5 to 25 mm is ceramsite. The material with a particle size greater than 25 mm is ceramsite blocks, which are crushed and used as building ceramsite sand material. They can also be used as adsorbent material. Example 2
[0057] Clayey shale, primarily composed of red, black, and green shale, supplemented by kaolin and bentonite, along with sludge and fly ash, was collected using conventional methods. The shale was then ground using a conventional vertical mill for 3-5 minutes, followed by the following steps: (1) Screen out shale and sludge fly ash with a particle size of less than 150 mesh; (2) Take 50 parts of the shale material screened in step (1), 30 parts of sludge and 20 parts of fly ash and put them into the mixer to mix evenly and stir into a mixture; the stirring time is 3 to 7 minutes. (3) The mixture described in step (2) is fed from its mixer into a storage tank for preheating and firing. (4) The mixture discharged in step (3) is directly fed into the kiln head feeding port of the three-stage transmission variable diameter rotary kiln. The three-stage transmission variable diameter rotary kiln is composed of three kilns of different diameters connected to each other. The total length of the rotary kiln is 77 meters, the diameter is 2.5 meters, the preheating zone is 56 meters, and the rest is the firing zone. The rotation speed of the rotary kiln is 1.5 revolutions / minute. It is dried by rolling towards the kiln head through the rotary kilns of different temperatures. The drying temperature is increased from the preheating temperature of 120℃ to 270℃. Then it enters the expansion zone and the sintering temperature is 1170℃ to produce 200 grade sludge fly ash ceramsite. (5) The sludge fly ash ceramsite blocks sintered in step (4) are sent to a cooler for cooling. The cooling time is 25 to 30 minutes to reduce the temperature of the sludge fly ash ceramsite blocks to below 100°C. Then, they are screened by a screening machine for secondary classification. The sieved material with a particle size of 0 to 5 mm is ceramsite sand, which can be used as building insulation mortar. The material with a particle size of 5 to 25 mm is ceramsite. The material with a particle size greater than 25 mm is ceramsite blocks, which are crushed and used as building ceramsite sand material. They can also be used as adsorbent material. Example 3
[0058] Clayey shale, primarily composed of red, black, and green shale, supplemented by kaolin and bentonite, along with sludge and fly ash, was collected using conventional methods. The shale was then ground using a conventional vertical mill for 3-5 minutes, followed by the following steps: (1) Screen out shale and sludge fly ash with a particle size of less than 150 mesh; (2) Take 40 parts of shale, 35 parts of sludge and 25 parts of fly ash after screening in step (1), put them into a mixer and mix them evenly to form a mixture; the mixing time is 3 to 7 minutes. (3) The mixture from step (2) is fed from its mixer into a storage tank for preheating and firing. (4) The mixture discharged in step (3) is directly fed into the kiln head feeding port of the three-stage transmission variable diameter rotary kiln and rolled towards the kiln head for drying through the rotary kiln at different temperatures; its drying temperature is increased from the preheating temperature of 120℃ to 270℃; then it enters the expansion zone sintering temperature of 1170℃ and is sintered to produce 200 grade sludge fly ash ceramsite. (5) The sludge fly ash ceramsite blocks sintered in step (4) are sent to a cooler for cooling. The cooling time is 25 to 30 minutes to reduce the temperature of the sludge fly ash ceramsite blocks to below 100°C. Then, they are screened by a screening machine for secondary classification. The particles with a screen size of 0 to 5 mm are ceramsite sand and can be used as building insulation mortar; those with a size of 5 to 25 mm are ceramsite; and those with a size greater than 25 mm are ceramsite blocks. After crushing, they can be used as building ceramsite sand materials or as adsorbent materials.
[0059] The performance of the 200-grade sludge fly ash ceramsite from Examples 1, 2, and 3 of this invention was tested according to the following standards: Lightweight aggregate GB / T17431 *1-1998; The test method for lightweight aggregate conforms to the national standard: Lightweight aggregate test method GB / T17431.2-1998.
[0060] The thermal conductivity of the sludge fly ash particles after calcination in Examples 1, 2, and 3 of this invention is 0.08 W / mK, 0.112 W / mK, and 0.3 W / mK, respectively. According to the test results, the 200-grade sludge fly ash ceramsite concrete prepared in Examples 1, 2, and 3 of this invention has a low thermal conductivity, with a tested thermal conductivity of 0.08–0.3 W / mK, while the thermal conductivity of ordinary sand and gravel concrete reaches over 1.9 W / mK. Building materials processed from the 200-grade sludge fly ash ceramsite of this invention, used in residential buildings, have an "automatic indoor temperature regulation" function, saving energy on indoor air conditioning and heating systems, resulting in significant energy savings. The test results also show that the particle structure characteristics of the sludge fly ash particles after calcination in Examples 1, 2, and 3 of this invention meet the requirements for thermal insulation materials.
[0061] Therefore, the performance test results of the 200-grade sludge fly ash ceramsite of the present invention meet the national standard: Lightweight Aggregate GB / T17431 *1-1998; the test method of lightweight aggregate meets the national standard: Lightweight Aggregate Test Method GB / T17431.2-1998.
[0062] The 200-grade sludge fly ash ceramsite prepared by this invention has a "honeycomb-like core" structure and a bulk density of less than 200 kg / m³. 3 Therefore, it is defined as Grade 200 sludge fly ash ceramsite. The concrete made from the Grade 200 sludge fly ash ceramsite and ceramsite sand of this invention has a specific gravity of 600-1200 kg / m³. 3 The specific gravity of ordinary sand and gravel concrete is 2,450 kg / m³. 3 ~2,500 kg / m 3 .
[0063] The sludge fly ash ceramsite produced by this invention can replace sand and stone as concrete aggregate; under certain geological load conditions, it can increase the number of floors and has good seismic performance; due to its light weight and low elastic modulus, it can withstand less seismic force and has a long natural vibration period under seismic load, absorb shock wave energy quickly, and has a good vibration reduction effect.
[0064] The 200-grade sludge fly ash ceramsite prepared by this invention is produced by high-temperature firing in a three-stage transmission variable-diameter rotary kiln at 1120°C to 1170°C. This results in a higher coefficient of expansion (1.5–3) and more stable product quality. The ceramsite sand can form better building insulation mortar. Blocks and wall panels processed from it have undergone a transformation, exhibiting properties such as aging resistance, corrosion resistance, frost resistance, and the absence of radioactive and harmful substances. In contrast, blocks made from ordinary waste residue do not retain these original properties.
[0065] Furthermore, its "honeycomb-like" particle structure gives it sound absorption and insulation properties. National building structure sound insulation standards require a hearing level of 40 decibels and a sound insulation level of 35 decibels. This type of wall and floor material is unique in that it fully meets or exceeds national building sound insulation and sound absorption standards without adding any additional sound insulation facilities. It is a green building material that prevents noise pollution and contributes to people's physical and mental health.
[0066] The 200-grade sludge fly ash ceramsite of this invention has a wide range of applications. It can replace sand and gravel as concrete aggregate, and can be prefabricated, cast-in-place, and pumped. It can also be widely used in 200-grade sludge fly ash ceramsite self-insulating blocks, self-insulating wall panels, floor slabs, self-insulating concrete, and ceramsite concrete beam and column aggregate. It can also be used in lightweight insulation boards, anti-freeze structures, and other types of building materials. It is an energy-saving, green, and environmentally friendly building material.
[0067] This invention relates to a 200-grade sludge fly ash ceramsite composition based on solid waste and its manufacturing method. The components, by weight percentage, include 38%–50% shale, 30%–40% sludge, and 20%–25% fly ash. The shale is a muddy shale primarily composed of red shale, black shale, and green shale, with kaolin and bentonite as secondary components, containing a total clay mineral content greater than 40% by weight. The method utilizes solid waste to manufacture 200-grade sludge fly ash ceramsite, making full use of solid waste resources, and features a simple process and low cost.
[0068] Using solid wastes such as fly ash, sludge, red mud, fly ash, construction waste, sulfonated mud, titanium gypsum, phosphogypsum, molybdenum tailings, gold tailings, and coal gangue as raw materials, this ceramsite utilizes the mineral components silicon, iron, aluminum, magnesium, sodium, potassium, calcium, and carbon contained in these solid wastes as the main components. The oxide composition of the ceramsite is as follows: silicon oxide 50%–60%, iron oxide 5%–8%, aluminum oxide 17%–23%, magnesium oxide 1%–3%, sodium oxide 1%–3%, potassium oxide 1%–3%, and calcium oxide 5%. The mixture contains 1%–10% carbon oxides and 1%–3% carbon oxides, with building foundation soil, subway tunnel soil, shale, and kaolin as auxiliary materials. Solid waste such as fly ash, sludge, red mud, construction waste, sulfonated mud, titanium gypsum, phosphogypsum, and molybdenum tailings are collected, crushed, aged, fermented, and screened. The resulting mixture is then added to a mixing chamber, granulated, sintered in a rotary kiln, unloaded, cooled, screened, inspected, and stored to obtain Grade 200 sludge fly ash ceramsite. This method utilizes solid waste to manufacture Grade 200 sludge fly ash ceramsite, making full use of solid waste resources. It produces ceramsite with a strength of 1-3 MPa and a bulk density ≤200 kg / m³. 3 200-grade sludge fly ash ceramsite.
[0069] This invention is not limited to the above-described optional embodiments. Anyone can derive other various forms of products under the guidance of this invention. However, regardless of any changes made in their shape or structure, any technical solution that falls within the scope of the claims of this invention shall be protected by this invention.
Claims
1. A 200-grade sludge fly ash ceramsite composition based on solid waste, characterized in that: It includes the following components: shale, sludge, and fly ash; The allocation of each group according to weight percentage is as follows: Shale 38%–50%; 30%–40% sludge; fly ash 20%–25%; The shale mentioned therein is a muddy shale composed of main components and auxiliary components, and the muddy shale contains more than 40% clay mineral components by total weight; The main components are red shale, black shale, and green shale, and the auxiliary components are kaolin and bentonite.
2. The 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 1, characterized in that: The shale, by weight percentage, comprises the following components: 50% ~ 60% Si02, 17% ~ 23% A1203, 5% ~ 8% Fe203, 1% ~ 3% MgO, 5% ~ 10% CaO and 1% ~ 3% (Na2CHK2O).
3. The 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 1, characterized in that: The shale, by weight percentage, comprises the following components: 58%Si02, 21%A1203, 6.8%Fe203, 2.4%MgO, 9%CaO, 1.5%Na20 and 1.3%K20.
4. A method for preparing a 200-grade sludge fly ash ceramsite composition based on solid waste, used to manufacture the 200-grade sludge fly ash ceramsite composition based on solid waste as described in any one of claims 1-3, characterized in that: The following steps are included: S1, Material preparation, collecting and selecting fine sludge, shale, sludge and fly ash raw materials; S2 uses a vertical mill to grind shale, sludge and fly ash raw materials respectively; S3, the ground raw materials are screened to obtain shale, sludge and fly ash materials with a mesh size of less than 150; S4, according to the proportion of the 200-grade sludge fly ash ceramsite composition based on solid waste as described in any one of claims 1-3, weigh shale, sludge and fly ash materials respectively, and transport them to a mixer for thorough mixing to obtain mixed raw materials, and transfer them to S5 or S6; S5, transport the mixed raw materials to the storage tank for storage and later use; S6 conveys the mixed raw materials to the three-stage drive variable diameter rotary kiln; S7. After drying, the mixed raw materials are preheated through the preheating heat plate. The temperature of the preheating heat plate is gradually increased from 120℃ to 270℃, and the preheating time is 40 to 45 minutes. S8, transfer to the firing zone, sinter at a temperature of 1120-1170℃ for 7-12 minutes, and obtain sludge fly ash ceramsite by sintering. S9, the sludge fly ash ceramsite is fed into the cooler, and the cooling time is 25 to 30 minutes, until the temperature of the sludge fly ash ceramsite drops below 100°C; S10, screen out ceramsite sand with a particle size of 0mm < ≤ 5mm, ceramsite with a particle size of 5mm < ≤ 25mm, and ceramsite blocks with a particle size of 25mm < ≤ 40mm; S11, Inspection: Ceramsite, ceramsite particles, and ceramsite blocks are stored separately. S12, ceramic sand is used as building insulation mortar; ceramic pellets and ceramic blocks are used as building materials or as adsorbent materials.
5. The method for preparing a 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 4, characterized in that: The aforementioned three-stage transmission variable diameter rotary kiln consists of three kilns of different diameters connected together: a drying kiln, a preheating kiln, and a sintering kiln.
6. The 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 4, characterized in that: The three-stage transmission variable diameter rotary kiln has a drying kiln diameter of 1.7 meters, a preheating kiln diameter of 2.1 meters, and a sintering kiln diameter of 2.5 meters.
7. The 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 4, characterized in that: The total length of the three-stage transmission variable diameter rotary kiln is 77 meters to 112 meters, of which the drying kiln has a length of 20 meters to 30 meters, the preheating kiln has a length of 20 meters to 30 meters, and the rest are sintering kilns.
8. The 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 4, characterized in that: The total length of the three-stage transmission variable diameter rotary kiln is 77 meters, of which the drying kiln has a straight length of 29 meters, the preheating kiln has a length of 27 meters, and the rest are sintering kilns.
9. The 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 4, characterized in that: The rotational speed of the three-stage transmission variable diameter rotary kiln is 1.5 rpm.
10. The method for preparing a 200-grade sludge fly ash ceramsite composition based on solid waste according to claim 4, characterized in that: The rotary kiln uses biomass gas as the combustion source, which provides a heat source for the firing of sludge fly ash ceramsite after combustion. The biomass fuel gas is generated by a biomass briquette pellet gasifier.
Citation Information
Cited By
Foamed concrete self-insulation building block based on 200-grade sludge ceramsite and preparation method of foamed concrete self-insulation building block
CN120887687A